Failure to identify antenatal multiple congenital contractures and fetal akinesia – proposal of guidelines to improve diagnosis. (7th January 2013) - Filges, Isabel; Hall, Judith G.
ABSTRACT Objective The aim of this study is to assess the rate of prenatal detection of multiple congenital contractures, to identify reasons for the failure of prenatal diagnosis and to propose the first guidelines to improve prenatal diagnosis. Method We evaluated records on 107 individuals recognized at birth to have Amyoplasia. We reviewed the literature on the onset and development of fetal activity, antenatal clinical signs in fetal movement disorders, prenatal studies of fetal movement and contractures by ultrasound and magnetic resonance imaging (MRI) and existing guidelines. Result In 73.8%, the diagnosis was missed prenatally. Correct diagnosis was achieved by the identification of bilateral clubfeet on ultrasound or because mothers perceived reduced fetal movement. Ultrasound would be able to visualize contractures, joint positioning, the quality of fetal movements, lung size, muscle tissue, and bone growth in the first or early second trimester. MRI results are promising. Guidelines for assessing early fetal movement do not exist. Conclusion Prenatal detection rate of multiple congenital contractures is appalling. Failure of diagnosis precludes further etiologic and diagnostic workup and deprives families of making informed pregnancy choices. Standards for prenatal diagnosis are lacking, but on the basis of current knowledge and expert opinion, we propose the first guidelines for a prenatal diagnostic strategy, discuss future directions and the need for multicentric studies. © 2013 John Wiley & Sons, Ltd.